2004
DOI: 10.1038/sj.jea.7500313
|View full text |Cite
|
Sign up to set email alerts
|

Ambient hydrogen sulfide, total reduced sulfur, and hospital visits for respiratory diseases in northeast Nebraska, 1998–2000

Abstract: This analysis examined associations between total reduced sulfur (TRS) and hydrogen sulfide (H 2 S) levels, and hospital visits for respiratory disease among residents of Dakota City and South Sioux City, Nebraska, from January 1998 to May 2000. For reference, the association between TRS, H 2 S, and digestive diseases was also examined. Time-series analyses of daily hospital visits in the selected outcome categories and measures of TRS and H 2 S were performed using generalized additive models with a Poisson l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 24 publications
0
40
0
1
Order By: Relevance
“…Reviews of the toxicity of H 2 S have been published (ATSDR, 1999;Bhambhani et al, 1997Bhambhani et al, , 1996Milby, 2000;Milby and Baselt, 1999;Burnett et al, 1977;Campagna et al, 2000). Clinical and research findings indicate that the nervous system is a target of H 2 S. At high concentrations, exposure can cause loss of consciousness or death (ATSDR, 1999).…”
Section: Article In Pressmentioning
confidence: 99%
“…Reviews of the toxicity of H 2 S have been published (ATSDR, 1999;Bhambhani et al, 1997Bhambhani et al, , 1996Milby, 2000;Milby and Baselt, 1999;Burnett et al, 1977;Campagna et al, 2000). Clinical and research findings indicate that the nervous system is a target of H 2 S. At high concentrations, exposure can cause loss of consciousness or death (ATSDR, 1999).…”
Section: Article In Pressmentioning
confidence: 99%
“…In Dakota City, Nebraska, ATSDR epidemiologists conducted health investigations focused on neurobehavioral and respiratory health outcomes after others in the agency had completed a separate exposure investigation Campagna et al, 2004). The earlier exposure investigation, conducted with the active involvement of local residents, had concluded that local exposures to hydrogen sulfide could pose a threat to public health (ATSDR, 1997).…”
Section: Relying On Relationships Developed By Othersmentioning
confidence: 99%
“…The U.S. Center for Disease Control (CDC) warns that brief exposures to high concentrations (>500 ppm) can cause unconsciousness or death (36). Campagna et al (37) have reported a correlation between elevated ambient H 2 S concentrations and hospital visits for respiratory diseases. Donham et al (38) reported that hydrogen sulfide and "manure gas" appeared to be the main toxic substance associated with death and illness for people with acute exposure to gases emanating from liquid manure.…”
Section: Agriculture and Its Contribution To Different Environmenmentioning
confidence: 99%